Anticoagulant and antibacterial activities of polysaccharides of red algae Corallina collected from Lebanese coast - Carine Sebaaly, Sahar Kassem, Elena Grishina, Hussein Kanaan, Alaa Sweidan, M. Said Chmit, Hussein M. Kanaan (Journal of Applied Pharmaceutical Science, 2014)
In this work, we studied another species of red algae, Corallina, growing on the Lebanese coast of Batroun. The analysis of trace elements showed that Corallina was rich in K, Ca, Mg, Na, Si, Sr, P and Fe. Corallina was composed of 70.81% of saturated fatty acids, 25.54% of monounsaturated fatty acids and 3.65% of polyunsaturated fatty acids with palmitic acid as the main component. Moreover, the total yield of sulfated galactans and carrageenan was 2.5% and 10%, respectively. Both extracts exhibited anticoagulant effect but sulfated galactans were less potent than carrageenan. Sulfated galactans possessed inhibitory activity as well as bactericidal activity against all Gram-positive strains tested (Enterococcus faecalis ATCC 29212 and Staphylococcus epidermidis CIP 444). But, carrageenan was only able to inhibit the growth of S. epidermidis with a minimal inhibitory concentration (MIC) of 0.325 mg/mL. Furthermore, infrared spectroscopy (IR) revealed that the isolated carrageenan was of Lambda-type. Corallina could therefore be considered as a potential source of bioactive molecules that may be useful for the development of new pharmaceutical agents.
Keywords: Red algae Corallina, sulfated galactans, carrageenan, antibacterial, anticoagulant.